On the biology, ecology and early stages of Rhagades (Wiegelia) predotae (Naufock, 1930) (Lepidoptera: Zygaenidae, Procridinae) - Efetov, K. A.; Tarmann, G. M. (SHILAP Revista de lepidopterología, 2020)
The full life-cycle of Rhagades (Wiegelia) predotae (Naufock, 1930) is described for the first time. The DNA- barcode of this species is provided. Prunus ramburii Boiss. as the larval host-plant is mentioned.